Oceanic protists with different forms of acquired phototrophy display contrasting biogeographies and abundance. Issue 1860 (16th August 2017) - Leles, S. G.; Mitra, A.; Flynn, K. J.; Stoecker, D. K.; Hansen, P. J.; Calbet, A.; McManus, G. B.; Sanders, R. W.; Caron, D. A.; Not, F.; Hallegraeff, G. M.; Pitta, P.; et al.
Abstract : This first comprehensive analysis of the global biogeography of marine protistan plankton with acquired phototrophy shows these mixotrophic organisms to be ubiquitous and abundant; however, their biogeography differs markedly between different functional groups. These mixotrophs, lacking a constitutive capacity for photosynthesis (i.e. non-constitutive mixotrophs, NCMs), acquire their phototrophic potential through either integration of prey-plastids or through endosymbiotic associations with photosynthetic microbes. Analysis of field data reveals that 40–60% of plankton traditionally labelled as (non-phototrophic) microzooplankton are actually NCMs, employing acquired phototrophy in addition to phagotrophy. Specialist NCMs acquire chloroplasts or endosymbionts from specific prey, while generalist NCMs obtain chloroplasts from a variety of prey. These contrasting functional types of NCMs exhibit distinct seasonal and spatial global distribution patterns. Mixotrophs reliant on 'stolen' chloroplasts, controlled by prey diversity and abundance, dominate in high-biomass areas. Mixotrophs harbouring intact symbionts are present in all waters and dominate particularly in oligotrophic open ocean systems. The contrasting temporal and spatial patterns of distribution of different mixotroph functional types across the oceanic provinces, as revealed in this study, challenges traditional interpretations of marine food web structures. Mixotrophs with acquired phototrophy (NCMs) warrant greater recognition in marine research.